Wyoming Sunrise: The Laws of Attraction - Book 2 - Connealy, Mary (Minneapolis, Minnesota : Bethany House, a division of Baker Publishing Group, 2023)
"When Nell becomes one of the first female Justices of the Peace in the country, she's immediately thrown into the fire. After an attempt is made on his life, widower Brand proposes a marriage of convenience to ensure his daughters will be taken care of-but as feelings grow, will this practical marriage become something more?"--
Keywords: Women tailors -- Fiction; Single fathers -- Fiction; Wyoming -- Fiction; Western fiction; Romance fiction; Novels